Biologics in pediatric psoriasis. - Oktem, A.; Kuscu, D.D.; Kundakcı, N. (European Journal of Pediatric Dermatology, 2023)
A third of cases of psoriasis begin in childhood and even at this age the disease can be associated with important psychological implications in young patients and even more in their parents. Biologics have forcefully entered the therapy of severe adult psoriasis, but they struggle to take off in the pediatric age. In the current study, biologics were used in 6/532 psoriatic patients under the age of 18. Adalimumab and other biologics were used at an average age of 13.1 years after an average of 7 years from initial diagnosis, proving to be effective and free from severe side effects.